2022
DOI: 10.3390/biomedicines10030566
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxic-Hyperoxic Exposures Effects in Patients with Metabolic Syndrome: Correction of Cardiovascular and Metabolic Profile

Abstract: The aim of this study was to evaluate efficacy and applicability of the “intermittent hypoxic-hyperoxic exposures at rest” (IHHE) protocol as an adjuvant method for metabolic syndrome (MS) cardiometabolic components. A prospective, single-center, randomized controlled clinical study was conducted on 65 patients with MS subject to optimal pharmacotherapy, who were randomly allocated to IHHE or control (CON) groups. The IHHE group completed a 3-week, 5 days/week program of IHHE, each treatment session lasting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…For instance, Bestavashvili et al showed higher absolute changes in tCh (-0.8 vs. 0.3 mmol/L), LDL-C (-0.8 vs. 0.3 mmol/L), and Tgl (-0.3 vs. 0.1 mmol/L) concentrations after 3 weeks (5 sessions•week −1 ) of IHHE (40-45 min, F i O 2 = 0.11-0.12 for 4-7 min, F i O 2 = 0.30-0.35 for 2-4 min) compared to a control group (sham IHHE: F i O 2 ~0.21 for 40-45 min) in patients with metabolic syndrome (Bestavashvili et al, 2021). Similar results were found by Bestavashvili et al in another study for tCh (-0.8 vs. 0.3) and LDL-C levels (-0.8 vs. 0.3) using a similar IHHE program in patients with metabolic syndrome (Bestavashvili et al, 2022). However, in both studies, the baseline lipid and lipoprotein concentrations (i.e., tCh, LDL-C and Tgl concentration) were statistically higher in patients who completed the IHHE program than in those who underwent sham IHHE.…”
Section: Systolic and Diastolic Blood Pressuresupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, Bestavashvili et al showed higher absolute changes in tCh (-0.8 vs. 0.3 mmol/L), LDL-C (-0.8 vs. 0.3 mmol/L), and Tgl (-0.3 vs. 0.1 mmol/L) concentrations after 3 weeks (5 sessions•week −1 ) of IHHE (40-45 min, F i O 2 = 0.11-0.12 for 4-7 min, F i O 2 = 0.30-0.35 for 2-4 min) compared to a control group (sham IHHE: F i O 2 ~0.21 for 40-45 min) in patients with metabolic syndrome (Bestavashvili et al, 2021). Similar results were found by Bestavashvili et al in another study for tCh (-0.8 vs. 0.3) and LDL-C levels (-0.8 vs. 0.3) using a similar IHHE program in patients with metabolic syndrome (Bestavashvili et al, 2022). However, in both studies, the baseline lipid and lipoprotein concentrations (i.e., tCh, LDL-C and Tgl concentration) were statistically higher in patients who completed the IHHE program than in those who underwent sham IHHE.…”
Section: Systolic and Diastolic Blood Pressuresupporting
confidence: 89%
“…The authors found no differences in blood concentrations of tCh, HDL-C, LDL-C, and Tgl between patients who completed an IHHE program (30–40 min, F i O 2 = 0.10–0.14 for 4–7 min, F i O 2 = 0.30–0.40 for 2–4 min) in addition to a multimodal training and those who completed a multimodal training only. In contrast, studies in patients with metabolic syndrome ( Bestavashvili et al, 2021 ; Bestavashvili et al, 2022 ), prediabetes ( Serebrovska et al, 2019 ), and coronary arteria disease ( Glazachev et al, 2017 ) found that IHHE promotes beneficial effects on patients’ lipid and lipoprotein profile. For instance, Bestavashvili et al showed higher absolute changes in tCh (-0.8 vs. 0.3 mmol/L), LDL-C (-0.8 vs. 0.3 mmol/L), and Tgl (-0.3 vs. 0.1 mmol/L) concentrations after 3 weeks (5 sessions∙week −1 ) of IHHE (40–45 min, F i O 2 = 0.11–0.12 for 4–7 min, F i O 2 = 0.30–0.35 for 2–4 min) compared to a control group (sham IHHE: F i O 2 ∼ 0.21 for 40–45 min) in patients with metabolic syndrome ( Bestavashvili et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, O 2 breathing goes beyond mere therapeutic use. Breathing an O 2 mixture at different concentrations, either hypoxic or hyperoxic, has been used for sport training [ 9 ], cardiovascular conditioning [ 10 , 11 ], or before extreme environmental exposure, such as SCUBA diving [ 12 , 13 ], military high-altitude free fall [ 14 , 15 ], or space flight [ 16 , 17 ], to avoid the occurrence of decompression sickness (DCS).…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent hypoxia-hyperoxia (IHH) is a modified IH protocol. The normoxia period is replaced by a moderate hyperoxia period (FiO 2 = 30-40%), resulting in a faster recovery from deoxygenation (Bayer et al, 2017;Glazachev et al, 2017;Dudnik et al, 2018;Serebrovska et al, 2019cSerebrovska et al, , 2022Afina et al, 2021;Behrendt et al, 2022;Bestavashvili et al, 2022). Compared with IH, IHH offers a more obvious improvement in the clinical parameters and is considered to offer more beneficial effects (Serebrovska et al, 2019a).…”
Section: Different Forms Of Intermittent Hypoxia Conditioningmentioning
confidence: 99%
“…IHH training in patients with coronary artery disease not only reduced blood pressure, but also improved exercise capacity, reduced angina attacks, enhanced the left ventricular ejection fraction, and reduced blood glucose (Glazachev et al, 2017). In patients with metabolic syndrome, IHH exposure can significantly reduce systolic and diastolic blood pressure (Bestavashvili et al, 2022). Mild IH can reduce blood pressure in patients with obstructive sleep apnea (OSA) complicated with hypertension (Panza et al, 2022).…”
Section: Intermittent Hypoxia and Hypertensionmentioning
confidence: 99%